2016
DOI: 10.1186/s11689-016-9157-6
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence for a parent-of-origin effect at the NOP9 locus on language-related phenotypes

Abstract: BackgroundSpecific language impairment (SLI) is a common neurodevelopmental disorder, observed in 5–10 % of children. Family and twin studies suggest a strong genetic component, but relatively few candidate genes have been reported to date. A recent genome-wide association study (GWAS) described the first statistically significant association specifically for a SLI cohort between a missense variant (rs4280164) in the NOP9 gene and language-related phenotypes under a parent-of-origin model. Replications of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 50 publications
(62 reference statements)
0
23
0
Order By: Relevance
“…The York cohort is a longitudinal cohort designed to study language and literacy development 37 and has been analyzed previously for genetic studies. 38 DNA was available for 103 families and a total of 318 individuals. Of these, phenotype data were available for N =103 probands and N =41 siblings.…”
Section: Methodsmentioning
confidence: 99%
“…The York cohort is a longitudinal cohort designed to study language and literacy development 37 and has been analyzed previously for genetic studies. 38 DNA was available for 103 families and a total of 318 individuals. Of these, phenotype data were available for N =103 probands and N =41 siblings.…”
Section: Methodsmentioning
confidence: 99%
“…While none of the genes that have been robustly implicated in language‐related disorders, e.g., FOXP2 and CNTNAP2 , are known to be imprinted (see the Supporting Information for a full list), there is evidence that others may be. One reason is the parent‐of‐origin effects identified in a number of genomic regions associated with language phenotypes, including significant paternal effects at 14q12, suggestive maternal effects at 5p13, and possible parent‐of‐origin effects in a chromosomal deletion in the 15q13.1–13.3 region, which might underlie different clinical manifestations for the same chromosomal rearrangement . While such parent‐of‐origin effects can arise from processes other than imprinting, it has been suggested that either imprinting or interactions with imprinted loci are the most likely explanations in these cases …”
Section: Inferring Selfishness Versus Altruism From Imprinted Genesmentioning
confidence: 99%
“…More generally, much still remains unknown about the genetic basis of linguistic behavior, and while it is known that certain aspects of the language phenotype are highly heritable, the currently known variants can only explain a small portion of this . Furthermore, the genome‐wide association studies often used to identify new variants rarely incorporate parent‐of‐origin effects that may be required to identify the contributions of imprinted genes, although there are exceptions . With improved statistical methods to discern different parental effects in association studies, this may prove a fruitful avenue for investigation.…”
Section: A New Approach To Understanding the Social Evolutionary Drivmentioning
confidence: 99%
“…As before, we selected among these genes those with a known role in brain oscillations. Finally, for SLI, we have mostly relied on the literature review provided by Chen et al (2017) and on the literature survey and results provided by Pettigrew et al (2016) , which contain candidates resulting from linkage analyses, GWA studies, and NGS analyses. As with DD, we surveyed the literature via PubMed looking for other candidates for this condition.…”
Section: Searching For Language Oscillogenome Candidatesmentioning
confidence: 99%